On Different Planes: An Organizational Analysis of Cooperation and Conflict Among Airline Unions - Perline, Martin M. (Relations industrielles / Industrial Relations, 1995)
On Different Planes: An Organizational Analysis of Cooperation and Conflict Among Airline Unions by David J. Walsh is reviewed.
Keywords: Airline industry; Airlines; Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z